INNOVATIVE METHODS OF TEACHING DESCRIPTIVE GEOMETRY IN HIGHER EDUCATION INSTITUTIONS - Svetlana Orynbaevna Atakhanova (Galaxy International Interdisciplinary Research Journal, 2022)
Descriptive geometry is one of the sections of geometry in which spatial figures, which are a collection of points, lines, surfaces, are studied by their flat images or projections. The main task of descriptive geometry is to compare a three-dimensional object with its flat projection model. Innovative methods of teaching descriptive geometry in universities require modernization.